The Potential of p38 MAPK Inhibitors to Modulate Periodontal Infections - Kirkwood, Keith L.; Rossa, Carlos [UNESP] (Bentham Science Publ Ltd, 2009)
Periodontal disease initiation and progression occurs as a consequence of the host immune inflammatory response to oral pathogens. The innate and acquired immune systems are critical for the proper immune response. LPS, an outer membrane constituent of periodontal pathogenic bacteria, stimulates the production of inflammatory cytokines IL-1 beta TNF alpha IL-6 and RANKL either directly or indirectly. In LPS-stimulated cells, the induction of cytokine expression requires activation of several signaling pathways including the p38 MAPK pathway. This review will discuss the significance of the p38 MAPK pathway in periodontal disease progression and the potential therapeutic consequences of pharmacological antagonism of this pathway in the treatment of periodontal diseases.
Keywords: Periodontal diseases; p38 MAPK; p38 inhibitors; innate immunity; inflammation; bone loss; cytokine; experimental periodontitis